The effects of 6 weeks of preseason skill-based conditioning on physical performance in male volleyball players - Trajkovic, N.; Milanovic, Z.; Sporis, G.; Milic, V.; Stankovic, R. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to determine the changes in physical performance after a 6-week skill-based conditioning training program in male competitive volleyball players. Sixteen male volleyball players (mean ± SD: age 22.3 ± 3.7 years, body height 190.7 ± 4.2 cm, and body mass 78.4 ± 4.5 kg) participated in this study. The players were tested for sprinting (5- and 10-m sprint), agility, and jumping performance (the vertical-jump test, the spike-jump test, and the standing broad jump [SBJ]). Compared with pretraining, there was a significant improvement in the 5- and 10-m speed. There were no significant differences between pretraining and posttraining for lower-body muscular power (vertical-jump height, spike-jump height, and SBJ) and agility. Based on our results, it could be concluded that a preseason skill-based conditioning program does not offer a sufficient stimulus for volleyball players. Therefore, a general conditioning and hypertrophy training along with specific volleyball conditioning is necessary in the preseason period for the development of the lower-body strength, agility and speed performance in volleyball players.